Immunostimulant activity of soybean milk against immunoglobulin (IgG, IgA) and lymphocyte cells proliferation of Balb/c mice induced hepatitis A - Ediati Sasmito; Sri Mulyaningsih; Eka Kartika Untari; Ratna Widyaningrum (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Soybean milk contains of isoflavon aglycon as genestein and rich of proteins. The genestein of soybean milk potentially has antitumor/anticancer, antivirus, antiallergic activities and immunity responses. The aim of this research was to evaluate the immunostimulant activity of soybean milk against immunoglobulin (IgG and IgA) and lymphocyte cells proliferation in Balb/c mice induced by hepatitis A. The test was done at 3 groups of 5 Balb/c mice. Each group was consummed orally with soybean milk(group I) dose of 0.7mL/20g/BW, levamisole (group II, as positif control) dose of 0,45 mg/0.7mL/20g/BW, and water (group III, as negative control) dose of 0.7mL/20g/BW, once a day, through out of the research. On the day of 7, 28 and boostered on the day of 43, all groups were induced intra peritoneally by hepatitis A dose of 5.24 IU/20g/BW. The serum were collected from plexus retroorbitalis by heparinized cappilary on the day of 14, 35 and 46, for IgG and IgA measured by ELISA method, and then the mice were sacrificed to isolate the lymphocytes of spleen. The lymphocyte cells proliferation measured by MTT-reduction method. The result shown that IgG and IgA increased significantly (p<0,05) against levamisole and water at the day-46, but did not increase significantly (p>0,05) against lymphocyte cells proliferation concerning with soybean milk consumed. It can be concluded that the immunostimulatory activity soybean milk was against humoral immunity, instead of seluler immunity.Key words : soybean milk, immunoglobulin, lymphocyte cells, hepatitis A, levamisole